MATHEMATICAL DETERMINATION OF SUBSIDENCE BREAK-POINTS IN ABANDONED OLD UNDERMINED REGIONS IN GIS SPACE FOR PURPOSES OF PEOPLE AND PROPERTIES PROTECTION - Sedlak, Vladimir (European Scientific Journal, ESJ, 2013)
For the environment protection, protection of people lives and their properties especially, it is necessary to recognize the mining subsidence, i.e. the fall depressions which are developed above mined out underground spaces in the earth surface as a natural continuation of dynamic tectonic processes. It is necessary primarily in the abandoned old undermined regions, where in a case of not protected entrance of persons there is increased danger of personal accidents and human lives threat and damage or destruction of properties. The limits of undermined regions in many cases equal to isolines connected so called break-points occurred in the front of the subsidence borders. The theory for the estimation of polynomial break-points in the case of subsidence analysis is presented. The theory was developed as a part of the kinematics analysis procedures for the evaluation of the magnesite mineral deposit Košice-Bankov, in the east of Slovakia. Some numerical and graphical results from the break-points estimation in the magnesite mineral deposit Košice-Bankov are presented. The obtained results are transformed into GIS in for a purpose of the environment protection.